Release Barabbas and turn him into Jesus? An analysis of the study of Neuroscience in Peruvian Criminal Law - Pisfil Casas, Stalin Einstein Anaxímenes (2023)
Science has generated a new way to restructure our thoughts and ideas, as well as improve the quality of human life. Thus, starting from the 20th century, neuroscience has aimed to study the nervous system, where the genesis of amalgams of emotions, thoughts, and the behaviors adopted by a person can be found. This scientific advancement has allowed us to reflect upon and question the theoretical foundations of Criminal Law, starting with concepts that have been documented in books, jurisprudence, and current criminal laws for years. Concepts such as punishment, its imposition, and the purpose of a sentence have been subject to debate. This leads us to question whether we can comprehend that a person who has committed a deliberate act with knowledge and intent should be condemned for their intentional actions or whether this behavior is the result of a neurological issue occurring in their brain.